2009
DOI: 10.1371/journal.pone.0005515
|View full text |Cite
|
Sign up to set email alerts
|

Abberant α-Synuclein Confers Toxicity to Neurons in Part through Inhibition of Chaperone-Mediated Autophagy

Abstract: BackgroundThe mechanisms through which aberrant α-synuclein (ASYN) leads to neuronal death in Parkinson's disease (PD) are uncertain. In isolated liver lysosomes, mutant ASYNs impair Chaperone Mediated Autophagy (CMA), a targeted lysosomal degradation pathway; however, whether this occurs in a cellular context, and whether it mediates ASYN toxicity, is unknown. We have investigated presently the effects of WT or mutant ASYN on the lysosomal pathways of CMA and macroautophagy in neuronal cells and assessed thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
321
1
17

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(357 citation statements)
references
References 63 publications
18
321
1
17
Order By: Relevance
“…In a cellular model of PD, transfection with Atg7 siRNA for 96 h did not induce cell death, even though autophagy acts cytoprotectively. We assumed that although activation of autophagy is cytoprotective when cells were damaged by aggresomes, the defect of the basal level of autophagy for a short time has no effect on the cell viability in cultured cell consistent with a previous report (32). Moreover, time course analysis showed that 12 h of treatment with CNP increased LC3-II level, and this effect did not continue until 48 h (data not shown) in HeLa cells.…”
Section: Volume 290 • Number 10 • March 6 2015supporting
confidence: 88%
“…In a cellular model of PD, transfection with Atg7 siRNA for 96 h did not induce cell death, even though autophagy acts cytoprotectively. We assumed that although activation of autophagy is cytoprotective when cells were damaged by aggresomes, the defect of the basal level of autophagy for a short time has no effect on the cell viability in cultured cell consistent with a previous report (32). Moreover, time course analysis showed that 12 h of treatment with CNP increased LC3-II level, and this effect did not continue until 48 h (data not shown) in HeLa cells.…”
Section: Volume 290 • Number 10 • March 6 2015supporting
confidence: 88%
“…The cellular clearance of ␣-synuclein is performed by the ubiquitin-proteasome system and chaperone-mediated autophagy (64), and interventions that stimulate chaperone-mediated autophagy can prevent ␣-synucleinopathy (65)(66)(67). Furthermore, aberrant ␣-synuclein inhibits the chaperone-mediated autophagy, which adds to the multitude of proposed mechanisms for its toxicity (68).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gaucher mutations were shown to lead to increased accumulation of α-Syn [69]. An α-Syn pathogenic cascade may include excess monomeric α-Syn interference at the synapse [70], and accumulation of stress-inducing phosphorylated, truncated, nitrated, or dopamine-conjugated α-Syn [71,72]. Excess α-Syn may also lead to misfolded α-Syn with increased potential to aggregate into intra-and extracellular toxic conformations.…”
Section: Pd and α-Syn As A Targetmentioning
confidence: 99%